Exploring undergraduate EFL students' perceptions and experiences of a Moodle-based reciprocal teaching application. (2nd January 2021) - Chang, Mei-Mei; Lan, Shu-Wen
ABSTRACT: This study reports on the use of Moodle as a platform for incorporating the online reciprocal teaching (RT) application into a freshman English Reading course in Taiwan. Data on the 53 students' perceptions and experiences of Moodle-based RT application were collected using a questionnaire, and their actual reading comprehension was measured via a pre-test and post-test consisting of multiple-choice questions and a summary-writing task. The results showed that the students perceived the Moodle-based RT application as a helpful learning method, and their scores on the multiple-choice comprehension tests were higher on the post-test than on the pre-test. However, the propositional density of the post-test summary texts was about the same as or lower than that of the pre-test summary texts, reflecting difficulties the students encountered in using written English to express their understanding of passages they had read. These findings offer implications for both EFL instructors and researchers, especially those interested in designing new college-level English reading courses or improving existing ones through the Moodle-based RT application.